1990
DOI: 10.1172/jci114765
|View full text |Cite
|
Sign up to set email alerts
|

Human very low density lipoproteins and chylomicrons can protect against endotoxin-induced death in mice.

Abstract: Endotoxemia stimulates many physiologic responses including disturbances in lipid metabolism. We hypothesized that this lipemia may be part of a defensive mechanism by which the body combats the toxic effects of circulating endotoxin. We tested the effects of mixtures of endotoxin, lipoproteins, and lipoprotein-free plasma and determined the ability of varying concentrations of human very low density lipoproteins (VLDL) and chylomicrons, as well as low density lipoproteins (LDL) and high density lipoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
232
1
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(243 citation statements)
references
References 40 publications
8
232
1
2
Order By: Relevance
“…Clearance of endotoxin is affected both by humoral inactivation and through uptake into liver and mononuclear phagocyte cells (17)(18)(19)(20), and is influenced by both host and LPS-specific factors (23,24). There is a complex relationship among binding of endotoxin to antibodies, to platelets, and to lipoproteins in the modulation of its biologic effects and clearance (23,24). Endotoxemia has been initially recognized in severe decompensated heart failure (4).…”
Section: Discussionmentioning
confidence: 99%
“…Clearance of endotoxin is affected both by humoral inactivation and through uptake into liver and mononuclear phagocyte cells (17)(18)(19)(20), and is influenced by both host and LPS-specific factors (23,24). There is a complex relationship among binding of endotoxin to antibodies, to platelets, and to lipoproteins in the modulation of its biologic effects and clearance (23,24). Endotoxemia has been initially recognized in severe decompensated heart failure (4).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the decrease in CETP levels, a decrease in hepatic lipase activity (7-10) may also serve to maintain HDL cholesterol levels by decreasing formation of remnant HDL 2 and thus decreasing clearance of HDL. Preserving HDL cholesterol levels during infection and inflammation may be important because of the ability of HDL to prevent the toxic effects of endotoxin (41)(42)(43) and reduce oxidative stress (44,45). Maintaining HDL cholesterol levels may also be important for delivery of cholesterol to peripheral tissues that may have increased needs for cholesterol during infection and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoproteins have been shown in in vivo and in vitro models to contribute to a reduction in LPS activity. 15,16) Moreover, it was reported that a low serum TC concentration indicated a worse prognosis in patients with severe heart failure 5,6) in ischemic as well as nonischemic heart diseases. The results of our study and these previous reports had the same conclusions for nonischemic (non-CAD) patients, but the results were quite different in ischemic (CAD) patients.…”
Section: General Findingsmentioning
confidence: 99%